Obtainable Drugs for Fish Hatchery Operation and Grow-out Ponds in Bangladesh - M. Ariful Islam; M. Nahid Hasan; Y. Mahmud; M.S. Reza; M.S. Mahmud; M. Kamal; Md. Shafiquzzaman Siddiquee (SCIENCEDOMAIN international, 2014)
This study was carried out to evaluate the obtainable drugs, chemicals and antibiotics used in aquaculture activities in Bangladesh for increasing aquaculture production. This study was carried out using data collection method through questionnaire interview and personal contact. The study was carried out in Mymensingh Sadar upazila and Trishal upazila of Mymensingh, Bangladesh from July 2011 to November, 2011. Data were collected through questionnaire interview, personal contact with hatchery and nursery owner as well as market survey with fish and shrimp farmers, retailers of animal medicine and representatives of pharmaceutical companies. About 46 questionnaires (16 pharmaceuticals companies, 14 drug traders/sellers, 10 fish farmers and 6 fish hatchery owners) were used to collect information. The study identified a number of commercial products with various trade names available in the market namely JV zeolite, geotox, green zeolite, orgavit aqua, fish vitaplus, AQ grow-G, oxyflow, oxy max and O2-marine which were most widely used. The survey discovered that 14 drug traders and 16 pharmaceuticals companies are actively involved in importing and marketing of the aqua drugs. Though Oxytetracycline and a potential sulfonamide are approved for the use of disease treatment but some off-labeled chemicals which had only trade name but no information about the active ingredient of these chemicals was discovered. The farmers of Bangladesh have little knowledge regarding the use of chemicals, their appropriate dose and method of application. For this perceptive the survey were taken so that the obtainable aqua drugs may be known as well as their appropriate dose and application method may be determined for safe aquaculture practices in Bangladesh.